Producer Price Index Manual : Theory and Practice. (Manuals and Guides, 2009)
The producer price index (PPI) measures the rate at which the prices of producer goods and services are changing overtime. It is a key statistic for economic and business decision making and inflation monitoring. The Producer Price Index Manual: Theory and Practice provides clear, up-to-date guidance on the concepts, uses, methods, and economic theory of the PPI, including information on classifications, sources, compilation techniques, and analytical uses of the PPI. The Manual supersedes the previous international guidance on PPIs (available in the Manual on Producers' Price Indices for Industrial Goods, published by the United Nations Statistics Division in 1979). The Manual's conceptual framework derives from the System of National Accounts1993 and recent developments in index number theory. Preparation of the Manual was undertaken by the Intersecretariat Working Group on Price Statistics through a technical expert group chaired by the IMF and involving representatives from the ILO, the OECD, the UN Economic Commission for Europe, the World Bank, national statistical offices, and academic institutions.